REVIEW OF THE PHYTOSEIIDAE MITES (ACARI: MESOSTIGMATA) ASSOCIATED WITH THE CAATINGA BIOME: DATA COMPILATION AND CHECKLIST - Araújo, Isaac Feitosa; Rodrigues, Jennifer Katia [UNESP] (Universidade Federal de Goias, 2023)
Brazil has a great diversity of mites of the Phytoseiidae family. The recognition of the hosts associated with this family is essential for applied biological control studies. The objective of this work is to compile data from the literature on the occurrence of phytoseiid mites Caatinga areas, in order to provide information on the current state of knowledge of the acarofauna in this biome. The data were obtained from the Phytoseiidae Database. Twentysix papers were compiled, covering 7 states and 84 municipalities. A total of 65 phytoseiid species belonging to 22 genera were recorded. The genera Amblyseius (18%), Neoseiulus (16%) and Euseius (9%) had the highest occurrence; at the species level E. concordis (33%), E. citrifolius (32%) and Neoseiulus idaeus (30%) had the highest number of records. Regarding hosts, 71 species from 24 different families belonging to 46 botanical genera were recorded in the study. The Solanaceae family (46%) had the most records, followed by Myrtaceae (20%) and Euphorbiaceae (18%). Solanum (38%) was the genus with more compiled records, at the species level Solanum paniculatum (23%) had more records. The present study contributed to the knowledge of Phytoeiidae species that occur in Caatinga areas.
REVISÃO DOS ÁCAROS PHYTOSEIIDAE (ACARI: MESOSTIGMATA) ASSOCIADOS AO BIOMA CAATINGA: COMPILAÇÃO DE DADOS E CHECKLIST
Keywords: acarofauna; Caatinga; data